Diffusion of process improvement methods in European SMEs. Issue 5 (2nd May 2017) - McGovern, Tom; Small, Adrian; Hicks, Christian
Abstract : Purpose: The purpose of this paper is to evaluate the European Regions for Innovative Productivity project that established Innovative Productivity Centres (IPCs) to assist SMEs in the North Sea Region of Europe to develop a process improvement capability. A conceptual framework explains how a process improvement methodology developed for large firms was adapted and shaped to meet the needs of SMEs. Design/methodology/approach: A comparative case study of 23 SMEs within six European countries. A protocol was developed to collect financial and operational data. This was supplemented by observations, secondary data and field notes. An established research model was used to evaluate the effectiveness and impact of the process improvement interventions. Findings: The intervention context and structure of the IPCs varied by country which shaped process improvement interventions at two levels: the country and the firm. During diffusion three process improvement variants emerged that were tailored to fit the local context. Developing a process improvement capability depended upon the availability of company resources, establishing KPIs and change agent support. Originality/value: The research contributes to knowledge and theory on diffusion and institutionalization by examining how SMEs responded to institutional pressures by implementing process improvement practices in different ways. Heterogeneity of both the IPCs and the external change agents were the drivers in shaping the improvement practices.